Brg1 Supports B Cell Proliferation and Germinal Center Formation Through Enhancer Activation - Schmiedel, Dominik; Hezroni, Hadas; Hamburg, Amit; Shulman, Ziv (Frontiers in Immunology, 2021)
Generation of protective antibodies depends on extensive rewiring of gene networks in B cells through changes in chromatin accessibility and conformation. The ATPase, Brg1, as part of the BAF chromatin remodeling complex, regulates chromatin structure, however, how Brg1 orchestrates gene expression that supports the adaptive immune response is unknown. Here, using Brg1-deficient B cells and analysis of vaccine-induced immune responses we find that Brg1 is required for B cell proliferation and germinal center formation through selective interactions with enhancer-promoter couplets that promote cell cycle-related gene expression. These findings reveal the role of Brg1 in vaccine-induced protection from pathogens.